Comparison between the LCST and UCST transitions of double thermoresponsive diblock copolymers: Insights into the behavior of POEGMA in alcohols - Roth, P.; Davis, T.; Lowe, Andrew (2012)
Doubly thermoresponsive polymers consisting of a poly[oligo(ethylene glycol) methyl ether methacrylate] (POEGMA) block displaying UCST behavior in alcohols and a block of poly(N-isopropylacrylamide) (PNIPAM) or poly(N,N-diethylacrylamide) (PDEAM), each of which has an LCST in water, were synthesized using RAFT polymerization followed by simultaneous activated ester/amine and nucleophilic thiol–ene postpolymerization conversions. Upon heating aqueous solutions of POEGMA-b-PNIPAM, 1H NMR spectroscopy confirmed a sudden decrease of the PNIPAM signals at the LCST, indicating dehydration and chain collapse. Dynamic light scattering (DLS) and turbidity measurements observed the macroscopic phase separation of the PNIPAM block at the same temperature. In 2-propanol, 1H NMR spectroscopy showed a gradual decrease of the POEGMA signals over a range of more than 30 °C during its UCST transition, indicating early stages of chain crumpling up to 20 °C above the macroscopic phase separation. The OEG side chains were found to collapse onto the backbone starting at the ester linkages, indicating the most unfavorable enthalpic polymer–solvent interactions occur adjacent to the ester group.Although the diblock copolymers displayed a strong concentration-dependent cloud point, 1H NMR spectroscopy revealed a concentration-independent desolvation, indicating the potential for applications that are not based on phase separation but on changes of polymer conformation. The phase separation occurred within a narrow temperature range of ∼6 °C as evidenced by turbidity and DLS. This transition could be exploited to self-assemble POEGMA-b-PDEAM into micellar structures with POEGMA cores in 1-octanol. Cooling to ∼15 °C below the cloud point was necessary to produce compact structures. Upon heating, the aggregates remained compact until redissolving entirely within a range of 1 °C, making the UCST of POEGMA in alcohols a valuable tool for reversible self-assembly applications.